A Multiple-Action Self-Healing Coating - Lutz, Alexander; van den Berg, Otto; Wielant, Jan; De Graeve, Iris; Terryn, Herman (Frontiers in Materials, 2016)
This paper describes a self-healing coating for corrosion protection of metals which combines two different types of self-healing mechanisms in one coating with multiple-healing functionality. 2-Mercaptobenzothiazole (MBT) was loaded into layered double hydroxide (LDH) carriers which were mixed into an acrylated polycaprolactone polyurethane based shape recovery coating and applied on Hot Dip Galvanized steel (HDG). The effect of triggered release of MBT on the protection of HDG became visible when samples with manually applied defects in the coating were immersed in 0.05 M NaCl solution (first, autonomous healing mechanism). The shape recovery (second, non-autonomous healing mechanism) was triggered by heating the samples for 2 minutes to 60°C. SEM-EDX and Raman Spectroscopy proved the presence of MBT in the LDH, in the MBT-loaded LDH in the coating and the released MBT on the HDG surface in the damaged area after being in contact with a solution containing corrosive ions. Electrochemical impedance spectroscopy (EIS) and scanning vibrating electrode technique (SVET) demonstrate the corrosion protection effect of MBT in the coating with a defect and the restoration of the barrier properties of the coating after defect closure. This way, the independent mechanisms of this multi-action self-healing coating could be demonstrated.